Relationship between very early brain structure and neuromotor, neurological and neurobehavioral function in infants born <31 weeks gestational age - George, J.; Fiori, S.; Fripp, J.; Pannek, K.; Guzzetta, A.; David, M.; Ware, R.; Rose, S.; Colditz, P.; Boyd, Roslyn (Elsevier Ireland Ltd, 2018)
Aim: This study aimed to examine associations between structural MRI and concurrent motor, neurological and neurobehavioral measures at 30–32 weeks postmenstrual age (PMA; ‘Early’), and at term equivalent age (‘Term’). Method: In this prospective cohort study, infants underwent Early MRI (n = 119; 73 male; median 32 weeks 1 day PMA) and Term MRI (n = 102; 61 male; median 40 weeks 4 days PMA) at 3 T. Structural images were scored generating white matter (WM), cortical gray matter, deep gray matter, cerebellar and global brain abnormality scores. Clinical measures were General Movements Assessment (GMs), Hammersmith Neonatal Neurological Examination (HNNE) and NICU Neonatal Neurobehavioral Scale (NNNS). The Premie-Neuro was administered Early and the Test of Infant Motor Performance (TIMP) and a visual assessment at Term. Results: Early MRI cerebellar scores were strongly associated with neurological components of HNNE (reflexes), NNNS (Hypertonicity), the Premie-Neuro neurological subscale (regression coefficient β = −0.06; 95% confidence interval CI = −0.09, −0.04; p < .001) and cramped-synchronized GMs (β = 1.10; 95%CI = 0.57, 1.63; p < .001). Term MRI WM and global scores were strongly associated with the TIMP (WM β = −1.02; 95%CI = −1.67, −0.36; p = .002; global β = −1.59; 95%CI = −2.62, −0.56; p = .001). Interpretation: Brain structure on Early and Term MRI was associated with concurrent motor, neurological and neurobehavioral function in very preterm infants.